The Effect of Earnings Management And Institutional Ownership On Company Value With Social Responsibility Disclosure As A Moderating - Wati, Erna; Jurnali, Teddy; Karjantoro, Handoko (Global Financial Accounting Journal, 2024)
Purpose: This study aims to provide empirical insight into the moderating role of CSR on the influence of earnings management and institutional ownership on firm value, and to evaluate whether CSR weakens or strengthens the impact of both factors. Research Method: This study uses a quantitative approach with secondary data from annual reports and sustainability reports of companies in the consumer non-cyclical and basic materials industry sectors listed on the Indonesia Stock Exchange for the 2021-2022 period with 263 data. Data analysis was carried out using multiple linear regression tests using the purposive sampling method. Findings: The results of the study indicate that earnings management has a significant negative effect on firm value, while institutional ownership does not have a considerable effect. CSR strategy is proven to moderate the relationship between earnings management and firm value positively but does not moderate the relationship between institutional ownership and firm value. Implication: This study provides insight for companies and investors about the importance of CSR management to increase firm value. In addition, regulators can consider these results to formulate better corporate governance policies.